Determination of Heavy Metals Concentration in Soil and Leafy Vegetables in Urban Expressway and Peri-urban Road Farms of Lagos State, Nigeria - Adewale, Peter Sanjo; Makinde, Sunday Clement Olubunmi; Kusemiju, Victor Owolola; Obembe, Olawole O. (Journal of Sustainability and Environmental Management, 2022)
Farmers have long considered urban agriculture as a panacea to urban food insecurity. However, growing food in cities is faced with many challenges like food contamination. Past studies on leafy vegetables focused on vegetables cultivated in urban centres. However, this paper aimed to determine and compare the level of heavy metals concentrations in soil and leafy vegetables in Urban Expressway Farms (UEF) and Peri-urban Road Farms (PRF) in Lagos, Nigeria. These two locations were purposefully selected. Soil Auger was used to drill holes to the required soil depth to collect soil samples. Sample of Amaranthus hybridus, Celosia argentea and Corchorus olitorius were collected using “envelope” principle. Pb, Cd and Mn residues in the samples were digested and determined using Atomic Absorption Spectrophotometer. The collected data were analysed using mean, standard deviation and Analysis of Variance. The mean pH value for UEF soil is 6.5 while PRF soil is 6.6. The highest Pb (0.93±0.06) was recorded in Celosia argentea at UEF. The highest mean concentration of Cd (0.51±0.11) was recorded in Amaranthus hybridus at UEF. The highest concentration for Mn was recorded in Amaranthus hybridus (0.98±0.02) at UEF. The concentrations of Pb in Celosia argentea at UEF 5 m from the expressway and Cd concentration in Amaranthus hybridus at 10 m from expressway were above the WHO/FAO permissible levels in vegetables. Level of heavy metal residue observed in soil and vegetables under this study were mostly influenced by the location of the farm-environment and not mainly the vegetable type. The relative concentrations of Pb and Cd in all the three leafy vegetables raise some serious environmental concerns and need to be monitored regularly to prevent consumption of contaminated leafy vegetables. Farmers are encouraged to cultivate in fields far away from expressway.